EFFORTS TO INCREASE LEARNING MOTIVATION AND LEARNING OUTCOMES THROUGH GOOGLE CLASSROOM DURING THE COVID-19 PANDEMIC - Cahyaningsih, Nabilla; Faslah, Roni; Sholikah (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2023)
This study aims to increase student learning motivation and learning outcomes by implementing the Blended Learning and Google Classroom system in the Office Management and Business Services Study Program of SMKN 14 Jakarta. The method in this study is Class Action Research which is carried out with 2 cycles. The subjects in this study were 35 students in archival subjects and the object of research was carried out at the time of the study. The data analysis technique used is descriptive quantitative by referring to the percentage paad as a measure of motivation level and through the evaluation of each meeting to measure learning outcomes. The results of this study on cyclical I were obtained an average learning motivation of 69% and learning outcomes with an average grade of 80.8. Of course, the situation in the first cycle experienced an increase of 29% for learning motivation and 7.8 points for the average class of learning outcomes. The second cycle experienced a 28% increase from the previous cycle with an average learning motivation